2016
DOI: 10.1111/bph.13628
|View full text |Cite
|
Sign up to set email alerts
|

Understanding how long‐acting β2‐adrenoceptor agonists enhance the clinical efficacy of inhaled corticosteroids in asthma – an update

Abstract: In moderate‐to‐severe asthma, adding an inhaled long‐acting β2‐adenoceptor agonist (LABA) to an inhaled corticosteroid (ICS) provides better disease control than simply increasing the dose of ICS. Acting on the glucocorticoid receptor (GR, gene NR3C1), ICSs promote anti‐inflammatory/anti‐asthma gene expression. In vitro, LABAs synergistically enhance the maximal expression of many glucocorticoid‐induced genes. Other genes, including dual‐specificity phosphatase 1(DUSP1) in human airways smooth muscle (ASM) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 282 publications
(427 reference statements)
1
60
0
1
Order By: Relevance
“…Thus, the net effect of regular SABA and LABA monotherapy could increase asthma severity and enhance mortality by preferentially enhancing proinflammatory gene expression. A genomic effect is also germane to the mechanism of action of ICS/LABA combination therapy, because glucocorticoids repress the expression of many of these adverse-effect genes (Newton and Giembycz, 2016) and protect against LABA-induced toxicity in asthmatic subjects (Cates et al, 2014). As a result, an ICS may tip the balance of a LABA away from side effects potentially toward therapeutic benefit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the net effect of regular SABA and LABA monotherapy could increase asthma severity and enhance mortality by preferentially enhancing proinflammatory gene expression. A genomic effect is also germane to the mechanism of action of ICS/LABA combination therapy, because glucocorticoids repress the expression of many of these adverse-effect genes (Newton and Giembycz, 2016) and protect against LABA-induced toxicity in asthmatic subjects (Cates et al, 2014). As a result, an ICS may tip the balance of a LABA away from side effects potentially toward therapeutic benefit.…”
Section: Discussionmentioning
confidence: 99%
“…An ICS can also augment, in an additive or synergistic manner, the expression of many LABA-induced genes that could be therapeutically desirable Newton and Giembycz, 2016). A recent microarraybased study using human airway epithelial cells identified many genes that are regulated in this way, including CRISPLD2, RGS2, and DUSP1 (Rider et al, under review).…”
Section: Discussionmentioning
confidence: 99%
“…This may, in part, explain the enhanced granulocyte (neutrophil/eosinophil) numbers observed in the BAL fluid of the HDM-exposed Rgs2 -/- animals. Furthermore, it is tempting to speculate that, in more severe neutrophilic asthma, the above effects of RGS2 could play a role in the enhanced clinical effectiveness of ICS/LABA combinations, compared to ICS as a monotherapy [42]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, DUSP1, which acts to reduce MAPK signalling, is induced by glucocorticoids and LABAs and may also reduce expression of inflammatory genes and provide bronchoprotection [6570]. In seeking to design improved glucocorticoids, and/or ICS/LABA combination therapies, we propose that strategies seeking to maximize expression of RGS2, and other beneficial gene products, may be therapeutically advantageous [42, 71]. …”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic value of combining long-acting β2-agonists with corticosteroids in the treatment of asthmatic patients is undeniable as evidenced by numerous reports showing better disease control, pulmonary function and reduced frequency of exacerbations (Newton & Giembycz, 2016). The mechanisms underlying the superior clinical benefits provided by the combination therapies have not been completely elucidated but several in vivo and in vitro studies have suggested that β2-agonists might possess antiinflammatory properties in addition to their bronchoprotective effect.…”
Section: -Therapeutic Actions Of β2-adrenoceptor Agonists In Asthmamentioning
confidence: 99%